(untitled) (The Pakistan Development Review, 1993)
My talk today is based on a research project, housed at the University of Pennsylvania, that we have undertaken for the UNFPA and UNDESD. The project, with the same title as the draft material distributed for this conference, is a collaborative effort among Lawrence Klein, Fred Campano, Dominick Salvatore, and myself. The principal issue in the project is the simultaneous interaction between demographic and socio-economic variables in the development process of an emerging economy. The main concrete objective is to construct an operational econometric framework which establishes appropriate feedback linkages between demographic and economic movements and allows meaningful examination of conflicts and consistencies of population policies with economic policies. This is essential in formulating appropriate population and other policies and in evaluating their effectiveness in promoting the demographic and socio-economic developmental goals of society.